Cortisol y prolactina en relación al estrés académico en adultos jóvenes. Una revisión sistemática - Salinas Cabrera, Margoth Alexandra (2023)
The stress is any situation that makes the body stay alert like feeling bad, or emotional disturbance, as a result, there is an interference with social life activity and those appear when a big change arrives or there is a big matter. The hormones involved are cortisol and prolactin, where cortisol has to do some functional activities when it is exposed to different stress situations, cortisol isthe stress hormone and a glucocorticoid arrives through the adrenal cortex, freeing some blood in a stressful situation; affecting the functions physiological, inflammatory and immunosuppressive, metabolism and the homeostasis, prolactin adenohypophysis that develops a function in the woman; to stimulate and keep the puerperal lactation, in man affect adrenal function, electrolytic balance, gynecomastia, and sometimes the galactorrhoea, decreased libido and other functions. This revision aims to obtain information about the cortisol and prolactin values related to academic stress in adults and young people in Latin America. In that way, it was established the revision methodology for systematic revisions began with the problem research taking into account the Cochrane system where more than 1500 articles could be found for the screening of information following the PRISMA method, which intervened and allowed the selection of 9, with the JBI tool the quality was qualified where it was possible to observe all of them with a low bias. A total of 9 articles were included in this review where the most influential factors such as lack of time, homework overload and exams, are the stressors with the greatest impact on student health. The young adult population is the most vulnerable since the levels of stress they present are high and moderate with greater frequency. Likewise, the relationship between the level of cortisol and prolactin with the level of stress that the young university student may develop is corroborated. In conclusion, it was found that the main factor that triggers stress in young university students is the lack of time, the level of stress that predominates in this population is high and moderate, and there is a close relationship between the values of the hormones involved with the level of stress that develops throughout the university career